PENGGUNAAN AUGMENTED REALITY UNTUK PEMILIHAN MASKER DENGAN METODE FACE TRACKING - Muhammad Pratiwo; Mutaqin Akbar (Universitas Islam Balitar, 2022)
When using a mask, appearance is essential for some people in supporting appearance and prioritizing comfort. However, when customer on trying masks, a prospective buyer must come directly to the pharmacy or shop. That’s can make consumers' time less efficient. In addition, trying a new mask also risks damaging the mask and an obligation to buy it. A mobile application with Augmented Reality features can help people see the appearance of masks on their facial contours via smartphones without trying it one by one. The application works by combining the mask model in the virtual world with the user's face in the real world captured by the user's smartphone camera. Literature study, needs analyze, application design, application development, and application testing are used in developing this application. Application development is carried out using the Augmented Reality face tracking method. From this application, mask model can be displayed right on the user's face on the android platform. In order to get optimal results, testing is done on the application by testing the application's compatibility when used on various Android devices and conducting a questionnaire to determine whether the application is well received by users using the User Acceptance Testing (UAT) and UAT results classified as good with a final score is 83 ,25%.